2015
DOI: 10.1186/s40814-015-0037-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bottle size on in-home consumption of sugar-sweetened beverages: protocol for a feasibility and acceptability study

Abstract: BackgroundIntake of free sugars in the population exceeds recommendations, with the largest source in the diet being sugar-sweetened beverages (SSBs). SSB consumption is linked to adverse health consequences and contributes to health inequalities, given greater consumption amongst the most deprived. One possible intervention is to reduce the available sizes of SSB packaging but there is an absence of evidence that this would reduce consumption. Based on evidence from studies targeting food consumption that peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The study design and methods have been previously published [15]. In brief, the study used a crossover design in which residential households received a set amount of cola each week for four weeks, based on their typical weekly purchasing, in bottles of one of four sizes: 1500 ml, 1000 ml, 500 ml, or 250 ml, in random order.…”
Section: Methodsmentioning
confidence: 99%
“…The study design and methods have been previously published [15]. In brief, the study used a crossover design in which residential households received a set amount of cola each week for four weeks, based on their typical weekly purchasing, in bottles of one of four sizes: 1500 ml, 1000 ml, 500 ml, or 250 ml, in random order.…”
Section: Methodsmentioning
confidence: 99%
“…the change-over was instantaneous with no washout. Following the procedures of a study using a similar design [26,27], at the end of each intervention fortnight, households were requested to pay for the wine they consumed, at the rate specified on the study wine list. To avoid any potential confounding impact of price on consumption with each bottle size, the amount they paid per litre was kept constant across the intervention periods.…”
Section: Stages 3 and 4: Intervention Periods-2 Weeks Each (4 Weeks Tmentioning
confidence: 99%
“…Another indirect examination of the inequality of SB consumption in the Colombian population also showed that there is no inequality in the classical sense; this finding was related to the pattern of snack food consumption [ 32 ]. The main measures taken to reduce the consumption of sugary drinks have focuses on SB, for example, by limiting bottle sizes [ 33 ] or regulating or even prohibiting the sale of SB at school stores to make consumption difficult [ 14 – 16 ]. SB consumption taxes are justified by the excess weight of the population and its role in health events associated with chronic disease [ 6 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%